AIR UNTUK TURKI, SURIAH, DAN IRAK: ANALISIS PENYEBAB TIDAK TERCAPAINYA WATER SHARING AGREEMENT NEGARA TEPI SUNGAI TIGRIS DAN EFRAT - Aulianisa Rahma Dyah Rusyadi; Mohamad Rosyidin; Satwika Paramasatya (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2022)
Transboundary river as a common water source has influenced the relations between riparian states. Especially when natural conditions have a dry climate, which has the potential to pose a threat of water scarcity. The utilization of the Euphrates and Tigris Rivers by Turkiye, Syria, and Iraq, is one illustration of the situation. Driven to maximize the use of water from the Euphrates and Tigris Rivers, the three countries are building hydrological projects such as dams. The development of the GAP sustainable dams project by Turkiye has in fact triggered protests from Syria and Iraq. This condition is influenced by the absence of a water sharing agreement between the three countries, so that unilateral use is unavoidable. This research aims to analyze the cause of water sharing agreement that hasn’t been achieved betweenTurkiye, Syria, and Iraq. This research is qualitative research by explaining the phenomenon using the desk research method. Based on the results of the study using Neorealism, the main cause of the failure of water sharing agreement between Turkiye, Syria, and Iraq is the anarchic international structure which is characterized by the absence of authority over the state, in such a way that it has shaped the behavior of the Turkiye, Syria, and Iraq to rely on themself to survive and achieve national interests. This condition makes Turkey, Syria, and Iraq difficult, even reluctant to cooperate.